2010
DOI: 10.3319/tao.2009.08.26.01(oc)
|View full text |Cite
|
Sign up to set email alerts
|

Scavenging Phenomenon Elucidated from 234Th/238U Disequilibrium in Surface Water of the Taiwan Strait

Abstract: Concentrations of dissolved (234 Th d) and particulate (234 Th p) 234 Th in surface water at 38 stations in the Taiwan Strait were determined for samples collected in May 2006. The spatial distribution of 234 Th in the Taiwan Strait is controlled by advective input of Kuroshio Branch Water via the Peng-Hu Channel and fast removal due to the high input of riverine particulates from the Cho-Sui River. A scavenging model involving physical transport was applied to the 234 Th d and 234 Th p data to estimate scaven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Therefore, the measurement of this POC flux is very important to understand the global carbon cycle and its response to climate change (Emerson et al 1997). Typhoons have a notable impact on POC flux, but one may ask the question how important are they around the world compared to other upwelling systems which are determined by either the sediment trap method or carbon budget (González et al 2000Olli et al 2001;Arístegui et al 2004;Monteiro et al 2006;Montero et al 2007;Thunell et al 2007;Chou et al 2009;Montes et al 2012) or 234 Th/ 238 U disequilibrium approach (Murray et al 1989;Bacon et al 1996;Moran et al 2005;Wei et al 2009Wei et al , 2010. We found that POC fluxes in this study after a typhoon are only less than POC fluxes reported in the Chukchi Sea ) and much higher than other POC fluxes in other locations (Fig.…”
Section: Implications For Poc Fluxes After Typhoon Eventsmentioning
confidence: 99%
“…Therefore, the measurement of this POC flux is very important to understand the global carbon cycle and its response to climate change (Emerson et al 1997). Typhoons have a notable impact on POC flux, but one may ask the question how important are they around the world compared to other upwelling systems which are determined by either the sediment trap method or carbon budget (González et al 2000Olli et al 2001;Arístegui et al 2004;Monteiro et al 2006;Montero et al 2007;Thunell et al 2007;Chou et al 2009;Montes et al 2012) or 234 Th/ 238 U disequilibrium approach (Murray et al 1989;Bacon et al 1996;Moran et al 2005;Wei et al 2009Wei et al , 2010. We found that POC fluxes in this study after a typhoon are only less than POC fluxes reported in the Chukchi Sea ) and much higher than other POC fluxes in other locations (Fig.…”
Section: Implications For Poc Fluxes After Typhoon Eventsmentioning
confidence: 99%
“…A Lagrangian observation by drifters deployed in October-November 1997 in the Central Taiwan Strait showed a strong current with a mean speed of 30~50 cm s -1 flowing northward in the Peng-Hu Channel (Chern and Wang, 2000) and, as a result of topographic influence, both the sb-ADCP data (Liang et al, 2003) and the drifter experiment (Tseng and Shen, 2003) revealed the strong landward flow at 24°10′ N. Accordingly, the DTh of 0.21 dpm L -1 and PTh of 0.45 dpm L -1 , respectively, obtained at 120°00′ E 24°00′ N (shown as C17 in Fig. 1, Wei et al, 2008b) were assumed to be the DTh and PTh of incoming water into the stations (B12, B13, D14, and B15) located in the central region. The flow field derived from the sb-ADCP data in the vicinity of JWR agreed with the direct current measured by current meter deployments at the JWR river mouth (our station D19) by Liu et al (2000).…”
Section: Th Scavenging and Removal Ratesmentioning
confidence: 91%
“…Since the direction of the average current at the stations to the north of station B9 are generally towards NNE (Table 2), so the dissolved and particulate 234 Th activities of 0.13 and 0.43 dpm L -1 , respectively, obtained at 121°30′ E 25°30′ N (shown as N30 in Fig. 1, Wei et al, 2008b) were assumed to be the destined DTh and PTh of outflow water from these stations. A Lagrangian observation by drifters deployed in October-November 1997 in the Central Taiwan Strait showed a strong current with a mean speed of 30~50 cm s -1 flowing northward in the Peng-Hu Channel (Chern and Wang, 2000) and, as a result of topographic influence, both the sb-ADCP data (Liang et al, 2003) and the drifter experiment (Tseng and Shen, 2003) revealed the strong landward flow at 24°10′ N. Accordingly, the DTh of 0.21 dpm L -1 and PTh of 0.45 dpm L -1 , respectively, obtained at 120°00′ E 24°00′ N (shown as C17 in Fig.…”
Section: Th Scavenging and Removal Ratesmentioning
confidence: 99%